2018
DOI: 10.1016/j.nedt.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery students' experiences of their clinical internship: A qualitative descriptive study

Abstract: The benefits and challenges associated with internship in midwifery are apparent, particularly when students' are contending with two geographically distant sites. Support mechanisms and suggestions for improvements are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 40 publications
0
53
1
2
Order By: Relevance
“…perceptions of life, relationships, achievement, and self. 42,43 Mollica and Hyman 44 reported that doing an internship positively affects the socialization and professional self-formation of nursing students.…”
Section: Students' Perceived Meaning Of Life Based On Personal Charmentioning
confidence: 99%
“…perceptions of life, relationships, achievement, and self. 42,43 Mollica and Hyman 44 reported that doing an internship positively affects the socialization and professional self-formation of nursing students.…”
Section: Students' Perceived Meaning Of Life Based On Personal Charmentioning
confidence: 99%
“…Midwives' attitudes during internship were investigated. Although this is a different health profession, the results also include the importance of internship in consolidating clinical skills, building trust and competencies relevant for midwifery practice (14). Not everything depends on the importance of mentoring.…”
Section: Question 10: a Brief Comment Of The Topic Your Attitude Exmentioning
confidence: 99%
“…This is the first paper which reports the experiences and opinions of midwifery students who completed such clinical training. The concept of mentoring in the education and training of nurses has been widely discussed reflecting numerous instances of its actual implementation, but there have been fewer published papers on mentoring for midwives and midwifery students [14][15][16][17][18][19][20]. We hope that this paper will fill a current gap in research.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the problem and knowledge retention are achieved, with focus on the 'Why', not just the 'What' and the 'How' [22][23][24]. Mentor-led clinical training has been seen by many nursing and midwifery educators as a solution leading to the improved acquisition of clinical skills and developing students' sense of empowerment [19,25,26]. Mentoring is defined as a relationship between a person who is just starting their career (mentee) and an experienced practitioner (mentor) who provides support, advice and knowledge which the mentee needs for her/his personal and professional development [27,28].…”
Section: Introductionmentioning
confidence: 99%